Home made Holland : how craft and design mix - Walrecht, Bernardine; Taylor, Louise (Islington : Crafts Council Gallery, 2002)
Home Made Holland brings together 30 contemporary designers from the Netherlands whose attitude to craft and traditional materials is reviving mainstream design.
Adlib record nr. 530009651
Engels
Home made Holland: how craft and design mix
kunstcatalogus
Keywords: Alberts, Christine; Annink, Ed; Bakker, Aldo; Bakker, Gijs; Bey, Jurgen; Brekveld, Arian; Constansia, Gonnie; Dolz, Dora; Eek, Piet Hein; Eichenberg, Iris; van Eijk, Kiki; van Eijk, Niels; Hackenberg, Gésine; Hans, Ineke; Heesen, Bernhard; van Hoff, Dick; Jongerius, Hella; Jongstra, Claudy; van Kouswijk, Manon; van Leuken, Kim; M3; Schie 2.0; Scholten & Baijings; Skujeniece, Mara; Studio Job; Vos, Roderick; Wanders, Marcel; Wiertz, Pauline; Wijsbeek, Rebecca; Zwändel; Nederland